Environmental mediation: an instrument for collaborative decision making in territorial planing - Caser, Ursula (2018)
Environmental Mediation allows, besides formal participation, true collaborative decision making as well as prevention and resolution of conflicts. This paper analyses the advantages of mediation applied in environmental and territorial planning conflicts (Mediação Ambiental e Sócio‑Territorial – MAST) following the requirements of the Portuguese Mediation Law No 29/2013, of April 19th. It aims to understand if this legal basis prevents or encourages a more intense and efficient use of Environmental Mediation in land use planning as a means within public policy.